Design and Implementation of IoT Integrated Water Management and Monitoring System - Caparida, Stefany Mae; Miano, Joel; Marajas, Antonio; Nabua, Michael; Caparida, Lomesindo (Journal of Information Systems Research and Practice, 2024)
Access to water is vitally important, especially for businesses and communities. It is an essential resource used for everyday living. Currently, the world faces a global water stress crisis that is worsening. This crisis occurs when communities cannot fulfill their water needs due to insufficient water supply. The Internet of Things (IoT) is a recent trend in technology today. IoT can provide new solutions to the water industry, addressing one of its biggest challenges: the inability to turn available data into insightful information for guiding organizational decision-making. In this study, the researcher envisions modeling a water management system. This system utilizes IoT technologies, including a LoRaWAN® Gateway Concentrator Module connected to a Wi-Fi router (enabling a large scale of wireless sensor connectivity), ESP8266 nodeMCU development boards, and flow sensors. Furthermore, in this model, the volume of water is measured using flow sensors. The collected water data is then transmitted to the cloud, accessible through a dashboard display that presents real-time data visualization. This study provides water organizations with a clear understanding of water utilization in an organization. It also facilitates easier monitoring of water usage, helping to identify possible unaccounted water. Thus, it promotes the effective use of our water resources.